Guidelines for Women’s Caucuses (2013)
The purpose of these Guidelines is to provide a practical tool for women seeking to create a women’s parliamentary caucus, or improve an existing caucus. They are intended to guide such initiatives, raising a series of key questions and examining all the aspects that need to be considered in creating and managing an effective caucus. We hope women parliamentarians will rely on these guidelines as a source of advice, examples of good practice, and, above all, of the inspiration needed to make their parliamentary terms a stimulating contribution to gender equality everywhere.